Transforming Islamic Religious Education Through Web-Based Learning: A Qualitative Study of Student Engagement and Learning Autonomy - Putra Ali Muhamad; Dewi Hasanah (WISE Pendidikan Indonesia, 2026)
This study explored the implementation of web-based learning in IRE, focusing on its contribution to student engagement and learning autonomy. A descriptive qualitative approach within an interpretivist paradigm was employed. Data were collected at Junior high school (SMP) Daarul Rahman Tempuling, Riau, Indonesia, through classroom observations, semi-structured interviews, document analysis, and field notes involving two Islamic Religious Education teachers, one school principal, and nine Grade VII students selected using purposive sampling. The data were analyzed using Braun and Clarke’s six-phase thematic analysis. The findings revealed three major themes. First, web-based learning transformed instructional practices by promoting more interactive, flexible, and student-centered learning through digital platforms such as Google Classroom, Google Forms, and YouTube. Second, although internet connectivity, digital literacy, and infrastructural limitations remained significant challenges, teachers adapted instructional strategies to sustain learning activities. Third, web-based learning enhanced student engagement and learning autonomy by encouraging active participation, improving access to learning resources, and extending learning beyond classroom instruction. This study contributes to the growing literature on digital learning in Islamic Religious Education by providing qualitative evidence that web-based learning can support pedagogical transformation while strengthening student engagement and independent learning within the context of Islamic junior secondary schools.